Decorating graphene with size-selected few-atom clusters: a novel approach to investigate graphene–adparticle interactions. Issue 29 (13th July 2017) - Scheerder, Jeroen E.; Picot, Thomas; Reckinger, Nicolas; Sneyder, Tomas; Zharinov, Vyacheslav S.; Colomer, Jean-François; Janssens, Ewald; Van de Vondel, Joris
Abstract : Preformed Au n clusters are deposited in a controlled fashion on graphene field-effect transistors. This hybrid system is characterized electronically and via electron microscopy. Abstract : We investigated the interaction between size-selected Au2 and Au3 clusters and graphene. Hereto preformed clusters are deposited on graphene field-effect transistors, a novel approach which offers a high control over the number of atoms per cluster, the deposition energy and the deposited density. The induced p-doping and charge carrier scattering indicate that a major part of the deposited clusters remains on the graphene flake as either individual or sub-nm coalesced entities. This is independently confirmed by scanning electron microscopy on the same devices after current annealing. Our novel approach provides perspectives for the electronic sensing of metallic clusters down to their atom-by-atom size-specific properties, and exploiting the tunability of clusters for tailoring desired properties in graphene.